Peranan Trans Jateng Kendal Terhadap Perubahan Sosial Masyarakat Kabupaten Kendal - Afifa Diana; Nuryani Nuryani; Waskito Waskito (Geography Education, Ivet University, 2021)
At present there are several types of transportation. There is one type of transportation called public transportation where passengers do not use their own vehicle when traveling. Kendal Regency as one of the densely populated areas has high traffic flow and community mobility, especially in the morning which is the start of activity and late in the afternoon the activity causes vehicles to stagnate, and also many public vehicles that carry passengers exceeding capacity. This requires adequate transportation services, both in number and ease. One example of public transportation is the existence of the Trans Jateng Bus which operates in Kendal Regency, which has been serving the community since October 28, 2019 with routes from Mangkang Terminal to Bahurekso Terminal. The purpose of this study is (1) to know the role of the Trans Kendal Central Java Towards Social Change in the Community of Kendal District, (2) to know what obstacles are faced in an effort to increase interest in using the Trans Kendal Central Java. This research is a qualitative research with descriptive analysis. With the method of observation, interviews, and documentation. The results of this study stated that there was a social change in the community that occurred with the presence of Trans Central Java, including high public enthusiasm balanced with infrastructure, tariffs, and comfortable service quality. In addition there are several obstacles encountered such as the absence of its own lane and bus delays.